FLEXIBLE ORGANIC PHOTOVOLTAICS - Kislyuk, V. V.; Kuznetsova О. Yu. (Science-based technologies, 2019)
The current issues in the field of flexible organic photovoltaic cells (OPVs) are reviewed. The inverted OPVs with conducting electrode of Al-doped ZnO electrode are argued on the basis of a numerous experimental evidences to be promising for low cost photovoltaic converters. Additional performance improvement of the OPVs is due to Al-containing nanospecies incorporated between the transparent electrode and the active layer. A technological rout is proposed for production of the low cost flexible power supplies promising for transport applications (e.g. airplanes) due to their light weight.